-4(-6x+2)-2x=4(x-3)-5

Simple and best practice solution for -4(-6x+2)-2x=4(x-3)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-6x+2)-2x=4(x-3)-5 equation:



-4(-6x+2)-2x=4(x-3)-5
We move all terms to the left:
-4(-6x+2)-2x-(4(x-3)-5)=0
We add all the numbers together, and all the variables
-2x-4(-6x+2)-(4(x-3)-5)=0
We multiply parentheses
-2x+24x-(4(x-3)-5)-8=0
We calculate terms in parentheses: -(4(x-3)-5), so:
4(x-3)-5
We multiply parentheses
4x-12-5
We add all the numbers together, and all the variables
4x-17
Back to the equation:
-(4x-17)
We add all the numbers together, and all the variables
22x-(4x-17)-8=0
We get rid of parentheses
22x-4x+17-8=0
We add all the numbers together, and all the variables
18x+9=0
We move all terms containing x to the left, all other terms to the right
18x=-9
x=-9/18
x=-1/2

See similar equations:

| (3^x+1)=28 | | 9x+17=-17+9x | | 2(2x+1)=10x | | 2s+6=5 | | 13x-9=7x+15 | | s+44=-1 | | t=55-9-3 | | 2(2-6x)=-4(3x-1) | | 40=-9q+q | | 57=10p+9p | | -4.5*x-8.9=12.6 | | z/32-2/8+7/8=13/16 | | 6a–2a=-36 | | 3z+z=20 | | 3(x–8)=3x+5 | | 5x+8-7x=-4x-1 | | 2(x-5)+1=3x-4 | | 30=6(c–3) | | 2k-7=15+k | | 4=13+9q | | -6(v+12)=-30 | | 0=q/2 | | 9x+2(5x+3)=30+7x | | -7=20-10x | | (x+2)-3=14 | | 2000x-0.03=6000 | | 5(d+6)=70 | | 35=-7y+14 | | (x+2)-3=14 | | 22-3c=13 | | 1+1x=7x-5 | | 7b+3-4b=3-3(b |

Equations solver categories